(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2016)
A completely randomized design (CRD) was used with a total of 160 day-old commercial broiler chicks which were randomly assigned to four treatment groups with five replicates into 20 pens and brooded. Feed and water were provided ad libitum. From day old chick to 21 day, the broiler chicks were fed Diet 1 (5% fish meal and 25% soybean meal, 1: 5), Diet 2 (3% fish meal and 30% soybean meal, 1: 10) was served as control diet, Diet 3 (2% fish meal and 30% soybean meal, 1: 15) and Diet 4 (1.5% fish meal and 30% soybean meal, 1: 20). From day 22 onwards, the broiler chicks were fed finisher diet, Diet 1 (5% fish meal and 25% soybean meal, 1: 5), Diet 2 (2.6% fish meal and 26% soybean meal, 1: 10, serve as control diet, Diet 3 (1.8% fish meal and 27% soybean meal, 1: 15) and Diet 4 (1.3% fish meal and 26% soybean meal, 1: 20). Weekly performances and mortality are measured. By feeding FS5 diet (5% fish meal and 25% soybean meal), the heavier body weight, increased feed consumption and feed conversion ratio of broiler chicks was observed when compared to that of other treatment groups. Conclusively, it is obvious that the ratio of dietary fish meal to soybean meal 1: 5 (FS5) improved body weight but the lower feed efficiency of this diet should be considered in economical point of view.